2005
DOI: 10.1097/01.bsd.0000137157.82806.68
|View full text |Cite
|
Sign up to set email alerts
|

Anterior-Only Stabilization of Three-Column Thoracolumbar Injuries

Abstract: Current types of anterior spinal instrumentation and reconstruction techniques can allow some types of unstable three-column thoracolumbar injuries to be treated in an anterior stand-alone fashion. This allows direct anterior decompression of neural elements, improvement in segmental angulation, and acceptable rates of arthrodesis without the need for supplemental posterior instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 42 publications
3
83
1
7
Order By: Relevance
“…Various intellectuals have reported that the occurrence ratio of lumber fractures is lesser in female patients. Similarly, thefindings of our research have also revealed the same phenomenon because 71% male patients were affected by SCREW TECHNIQUE OUTCOMES 721 5 lumber fractures as compared to that of 29 % comprising of female patients. Erozlu, Ozturk, and Aydinili also discussed the resembling results in their research for lumbar spine burst fractures and theaverage age of observed population was 12.5±4 years (Range_UL15-LL79).…”
Section: -23supporting
confidence: 63%
“…Various intellectuals have reported that the occurrence ratio of lumber fractures is lesser in female patients. Similarly, thefindings of our research have also revealed the same phenomenon because 71% male patients were affected by SCREW TECHNIQUE OUTCOMES 721 5 lumber fractures as compared to that of 29 % comprising of female patients. Erozlu, Ozturk, and Aydinili also discussed the resembling results in their research for lumbar spine burst fractures and theaverage age of observed population was 12.5±4 years (Range_UL15-LL79).…”
Section: -23supporting
confidence: 63%
“…The anterior approach to the thoracolumbar spine was first developed by Hodgson and Stock, who advocated it primarily for the drainage of tuberculous abscesses (Sasso et al, 2005). The retroperitoneal approach to the thoracolumbar spine for the decompression of late, malunited burst fractures, usually those associated with kyphotic deformity and canal encroachment, was developed by Bohlman (Fontijne et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal approach can be used to place fixation screws as high as L2. Fractures of L2 and L3 are managed using a subdiaphragmatic retroperitoneal approach (Sasso et al, 2005). Attempting screw placement into L1 is hindered by the superior margin of the wound and may result in screws being placed obliquely rather than parallel to the endplates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Anterior approach provides a more direct and complete decompression of the spinal canal, potentially allowing a better neurological outcome. 6 So surgical corpectomy of the compromised anterior column requires reconstruction.…”
Section: Introductionmentioning
confidence: 99%